BREAST SELF-EXAMINATION STUDY ON KNOWLEDGE AND PERCEPTIONS ABOUT BREAST CANCER IN WOMEN OF RELIABLE AGE AT THE YUSRA CAKUNG MIDWIFERY CLINIC - Susanti, Eva; Indawati, Eli (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2024)
Disease cancer is reason death number two in the world after disease cardiovascular. Reason biggest death consequence cancer Among other things, it is caused by cancer lung, cancer colorectal, liver cancer and cancer breast. Cancer breast is the most common cancer and is reason death biggest Because cancer among people women all over the world so moment This cancer breast Still become problem health major in the world. Study This aim For know the Examination Study Breast Alone To Knowledge And Perception About Cancer Breasts in Aged Women Fertile at the Yusra Cakung Midwife Clinic. Study This using quasi experimental with purposive sampling with a sample of 64 people. Data engineering included in analysis univariate use distribution frequency and analysis bivariate use calculation SPSS program statistics . Based on the results of research regarding self-breast examination studies on knowledge and perceptions about breast cancer in women of childbearing age at the Midwife Yusra Clinic, obtained results that age, occupation, source information, and history disease own impact positive and significant to knowledge and perception patient about inspection breast Alone with P-Value < 0.05. Whereas level education own impact negative with P-Value > 0.05.